(untitled) (Studia Prawnicze / The Legal Studies, 2006)
Po upływie półrocznego vacatio legis, dnia 7 marca 2006 r. weszła w życie uchwalona przez Sejm ustawa z dnia 7 lipca 2005 r. o działalności lobbingowej w procesie stanowienia prawa. Przypomnijmy, że wymieniona ustawa jest wynikiem realizacji drugiej z kolei próby uregulowania przez Sejm zasad działalności lobbingowej w Polsce. Pierwsza próba została podjęta w Sejmie III kadencji. W poselskim projekcie ustawy (, o jawności procedur decyzyjnych, grupach interesów i publicznym dostępie do informacji"), wniesionym do Sejmu III kadencji dnia 20 lipca 2000 r., działalność „lobbyingową" zdefiniowano jako „każde działanie, którego celem jest w ramach obowiązującego prawa - wywarcie wpływu na organy władzy i administracji publicznej, zmierzające do przekonania do pewnej racji - swojej lub wyrażanej przez grupę interesów In the legislative process, on 7 July 2005 the Sejm (the lower chamber of the Polish parliament) passed the Act on Lobbying Activities, which came into force on 7 March 2006. In the article are analysed the circumstances which brought about preparations in the Sejm of III and IV term of the bills regulating the principles of lobbying activities and in this context was examined the legislative object of the passed bill. Further is discussed the range of regulations contained in the six chapters of the act. Analysed in detail are the transparency principles of lobbying activities and the mechanisms which function in their realisation, among other things are discussed making drafts of legislative acts available to public and carrying out public hearings. The legal articles which regulate the principles of professionally conducted lobbing activities, the control over them and the act which provides for sanctions for violations, are elaborated. Next, the catalogue of issues which may hinder application of the act and achieving anticipated objectives is formulated. Since, as the author claims, the Act on Lobbing Activities constitutes legislative experiment, then when its regulations come into force, it will become an experiment itself in the scope of its application in the practical, public and political relations.